2015
DOI: 10.5433/1679-0359.2015v36n5p3329
|View full text |Cite
|
Sign up to set email alerts
|

Perfil hematobioquímico e produção de leite de vacas mestiças Girolando suplementadas com resíduo de caju desidratado

Abstract: This paper aims to evaluate the influence of different levels of supplemental product-dehydrated cashew in the feed for crossbred Girolando cows on milk production and hemato-biochemical profile. The experiments were conducted using eight cows that were randomly distributed in a Latin square design (4×4), in which treatments consisted of four supplementation levels with product-dehydrated cashew (PDC) in animal diets, namely: 0% PDC (control diet), 1.0 kg of DCP, 1.5 kg of PDC and 2.0 kg of PDC in total dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In addition, dehydrated passion fruit residue can increase the free tannins, which can negatively affect fibrolytic bacteria by changing their membranes (Makkar, 2003). Some researchers have reported that the presence of a high tannin concentration (>50 g/kg DM) in fruit residues results in the inhibition of voluntary intake and increases the number of chews and bolus chewing time due to astringents resulting from the formation of complexes by salivary proteins and tannins (Muir, 2011;Bezerra et al, 2015;Gxasheka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dehydrated passion fruit residue can increase the free tannins, which can negatively affect fibrolytic bacteria by changing their membranes (Makkar, 2003). Some researchers have reported that the presence of a high tannin concentration (>50 g/kg DM) in fruit residues results in the inhibition of voluntary intake and increases the number of chews and bolus chewing time due to astringents resulting from the formation of complexes by salivary proteins and tannins (Muir, 2011;Bezerra et al, 2015;Gxasheka et al, 2015).…”
Section: Discussionmentioning
confidence: 99%